Edible Mushrooms of Ecuador: consumption, myths and implications for conservation - Gamboa-Trujillo, Paúl; Wartchow, Felipe; Cerón-Martinez, Carlos; Andi, Domingo; Uwinjin, Pedro; Grefa, Gladys; Entza, Maria; Chimbo, Eulalia; Chimbo, Julio; Payaguaje, Joaquina; Piyaguaje, Norma; Payaguaje, Delfin; et al. (Ethnobotany Research and Applications, 2019)
Background: Ecuador is divided into three geographical regions: Amazon, Coast and Mountains, on which one having its own empirical knowledge and traditions in relation to their natural environments. Studies about traditional knowledge of macrofungi were initially carried out in the Brazilian Amazon and later in Colombia, Guyana and Venezuela. In Ecuador few studies have been published. Thus, the aim of this study is to investigate many ethnomycological data of the edible mushrooms used by several ethnic Ecuadorian groups, discussing the meanings of species’ vernacular names and related myths. Methods: The ethnomycological data of the edible mushrooms were collected in 13 indigenous communities of Ecuador during periods of high rainfall from 2002 to 2016, with interviews and forums. Additionally, the fungal specimens were collected, and voucher deposited at Herbarium QAP. Results: Thirty-seven edible species of macrofungi were identified and some of them are discussed in relation to aspects like local peoples’ mythologies, habits or tradition, their preparation for consumption and myths. Thus, this research added new several ethnomycological data and helped to understand the mycophagous behavior in Ecuador. Conclusions: These studies should continue in order to prevent ethnobiological loss caused by the degradation of the environment in which these people live, causing a loss of the biodiversity. In addition, biological conservation of these ecosystems is urgent since many natural resources are used for these indigenous communities as food consumptions. Key words: Amazonia, biodiversity, Coast, Fungi, Páramos, South America